(untitled) (Práxis Educativa, 2023)
This text aims at analysing the aspects highlighted in research on Basic Education and the pandemic, carried out between 2020 and 2021. Of qualitative nature, exploratory character and state-of-the-art type, the study located five dissertations and 19 articles in A1 and A2 journals, according to the Qualis Capes 2013-2016. Data treatment followed the steps suggested by Romanowski and Ens (2006). The analysis especially considered the contributions of Chauí (2020), Freire (2015, 2017), Freire and Shor (1987), Saviani and Galvão (2021), among others. It was possible to notice that the dilemmas of Remote Teaching were quite present, evidencing inequalities and difficulties of differentiation between Emergency Remote Teaching and Distance Education. The challenges of teaching and learning alert for the need to review education policies, pedagogical practices, and teacher training to cope with future crossings that may affect the daily school life. Keywords: Remote Teaching. Basic Education. Teaching practice.